1978
DOI: 10.1111/j.1432-1033.1978.tb12264.x
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Daunomycin with Polydeoxynucleotides

Abstract: The ability of daunomycin to bind to various DNA polymers has been studied by thermal denaturation, spectrophotometric analysis and inhibition of the polymerisation reactions catalysed by Escherichia coli DNA polymerase I and rat liver DNA polymerase CI. The quantitative binding measurements revealed that the antibiotic binds tightly to all synthetic polydeoxynucleotides studied.The results demonstrated that daunomycin can bind with equal affinity to dG . dC or dA . dT basepaired sequences. However, the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…The difference in the exclusion parameter is essentially the same as that reported here. Phillips et al (1978) reported equal binding affinities for the interaction of daunomycin with the same series of deoxypolynucleotides used in this study. They did note, however, differences in the apparent site size, which roughly followed the trend reported here.…”
Section: Discussionmentioning
confidence: 65%
“…The difference in the exclusion parameter is essentially the same as that reported here. Phillips et al (1978) reported equal binding affinities for the interaction of daunomycin with the same series of deoxypolynucleotides used in this study. They did note, however, differences in the apparent site size, which roughly followed the trend reported here.…”
Section: Discussionmentioning
confidence: 65%
“…Adriamycin was reported to inhibit the activities of DNA polymerases (Goodman et al, 1974;Zunino et al, 1975b) and RNA polymerases (Zunino et al, 1975a), presumably by the mechanism of insertion of the drug molecule into the double helix of DNA, as has been demonstrated for daunorubicin (Ward et al, 1965;Pigram et al, 1972;Phillips et al, 1978).…”
Section: Discussionmentioning
confidence: 84%
“…We shall mention here only some of the most representative results. Early (1978) thermal denaturation studies, spectrophotometric analysis and inhibition of polymerisation reactions indicated equal binding affinities of DNM for poly(dG-dC)·poly(dG-dC) and poly(dA-dT)·poly(dA-dT) but a significantly greater affinity for these alternating copolymers than for the poly(dA)·poly(dT) homopolymer (7). Competition dialysis experiments (8) indicated a preference of DNM for rich DNA's and were originally interpreted as indicating a preference of DNM for the G-C base pair.…”
Section: Introductionmentioning
confidence: 97%